URINALYSIS IN CLINICAL LABORATORIES DIAGNOSTIC IMPORTANCE AND TECHNIQUES - Tolibova Dilshoda,; Nurmatova M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Urinalysis is one of the most commonly performed diagnostic tests in clinical laboratories. It provides valuable information regarding the functioning of the kidneys, urinary tract, and other metabolic processes within the body. Through physical, chemical, and microscopic examination of urine, clinicians can detect a wide range of disorders, including urinary tract infections (UTIs), kidney diseases, diabetes, and systemic conditions such as hypertension.This article aims to explore the diagnostic importance of urinalysis in clinical practice, focusing on the various techniques used for urine analysis, the types of abnormalities detected, and their clinical significance. The role of urinalysis in detecting early-stage diseases and monitoring treatment efficacy will also be discussed. By understanding the various components of urinalysis, healthcare professionals can make informed decisions about diagnosis and treatment.[1]